2022
DOI: 10.3390/diagnostics12102303
|View full text |Cite
|
Sign up to set email alerts
|

Electric Source Imaging in Presurgical Evaluation of Epilepsy: An Inter-Analyser Agreement Study

Abstract: Electric source imaging (ESI) estimates the cortical generator of the electroencephalography (EEG) signals recorded with scalp electrodes. ESI has gained increasing interest for the presurgical evaluation of patients with drug-resistant focal epilepsy. In spite of a standardised analysis pipeline, several aspects tailored to the individual patient involve subjective decisions of the expert performing the analysis, such as the selection of the analysed signals (interictal epileptiform discharges and seizures, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Several aspects tailored to the individual patient involve subjective decisions of the expert performing the analysis. A recent study, which included 25 consecutive patients analyzed by six different experts, showed that when experts used the same analysis pipeline and same software, the inter-analyzer agreement was substantial [15]. These results support the need for standardization in ESI methodology, applied in clinical practice.…”
Section: Electroencephalogram Source Imagingmentioning
confidence: 65%
“…Several aspects tailored to the individual patient involve subjective decisions of the expert performing the analysis. A recent study, which included 25 consecutive patients analyzed by six different experts, showed that when experts used the same analysis pipeline and same software, the inter-analyzer agreement was substantial [15]. These results support the need for standardization in ESI methodology, applied in clinical practice.…”
Section: Electroencephalogram Source Imagingmentioning
confidence: 65%
“…The evaluators' confidence in the method was based on the literature on EEG-fMRI, which showed the frequent but far from perfect concordance of BOLD responses with epileptic foci 28 as well as personal experience in their clinical practice. A similar methodology has been used in evaluating EEG-fMRI for surgery, 29 the contribution of EEG source analysis, [30][31][32] resting-state functional connectivity, 33 and interictal PET findings. 34 The current study demonstrates that EEG-fMRI provides additional value when combined with traditional pre-surgical investigations of medically refractory epilepsy by increasing confidence in the identification of epilepsy syndrome, localization, and surgical candidacy.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluators' confidence in the method was based on the literature on EEG‐fMRI, which showed the frequent but far from perfect concordance of BOLD responses with epileptic foci 28 as well as personal experience in their clinical practice. A similar methodology has been used in evaluating EEG‐fMRI for surgery, 29 the contribution of EEG source analysis, 30 , 31 , 32 resting‐state functional connectivity, 33 and interictal PET findings. 34 …”
Section: Discussionmentioning
confidence: 99%